Assessment of the residential radon concentrations in the Bakony Region, Hungary - Zsolt Homoki; Gergely Tóth; Anita Csordás; Edit Tóth-Bodrogi; Miklós Hegedűs; Tibor Kovács (Radiation Medicine and Protection)
Objective: To investigate the current levels of indoor radon activity in the geologically complex Bakony Region of Hungary, which has been historically affected by industrial activities, and to identify areas that may require further monitoring and intervention. Methods: Experiments were carried out to measure quarterly indoor radon activity concentrations in ground-floor dwellings for a year using CR-39-type nuclear track detectors at 30 locations in 9 settlements to provide current information on the Bakony Region and identify areas requiring further attention. Results: Since the annual average indoor radon activity concentration in the Bakony Region was 86 Bq/m3 and the maximum 274 Bq/m3, that is, less than the 300 Bq/m3 national and EU reference levels, it is considered safe. Two locations were equal to or exceeded the reference level during part of the year. While most of the Region exhibited high radon concentrations in the autumn and winter, two settlements presented inverse seasonal variations. Conclusion: Although the autumn and winter values yielded a strong correlation with the annual mean and each other, this was not the case regarding the summer and spring values. The annual mean effective dose for the Region from the inhalation of radon and its progenies was estimated to be 2.2 ​mSv/year.